A general high-efficiency procedure for production of microcell hybrids. - Fournier, R E (1981)
The relative efficiency of microcell-mediated chromosome transfer vs. somatic cell hybridization has been determined. The prolonged mitotic arrest generally used to micronucleate donor cells also reduced the fusion efficiency to 1/10th-1/5th of that in whole cell hybridizations. Here we report an alternative micronucleation protocol, involving sequential treatment of the donor cells with Colcemid and cytochalasin B, which yielded micronucleated cells that hybridized with the same efficiency as whole cells. The enucleation, purification, and fusion steps of the microcell procedure have also been refined. By using these modifications the practical yield of microcell hybrid clones can be increased 50- to 100-fold.